Adverse effects of endocrine therapy in breast cancer: single institute experience - Sert, Fatma; Ozsaran, Zeynep; Esen, Erhan; Alanyalı, Senem; Sert, Ismail; Haydaoglu, Ayfer; Aras, Arif (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: The main purpose of this study is to assess the known adverse effects of adjuvant endocrine therapy for non-metastatic breast cancer patients and to present our single center experience with light of literature. Material and methods : The breast cancer patients treated with adjuvant radiotherapy in Medical School of Ege University between January 2007 and December 2009 were evaluated for this trial after obtaining their acceptance. Vital findings, bone mineral densitometry, endometrium thickness measured with trans-vaginal ultrasonography, biochemical results including liver function tests and blood lipid profile (total cholesterol, HDL, LDL, VLDL, triglyceride) were recorded for each controls. Socio-demographic data, financial statuses, medical history, co-morbid diseases were obtained from first controls. Patients were followed without any local recurrence and distant metastases until June 2011. Results: Endometrium thickness was not seen in AI using patients. As compared with tamoxifen group, lack of thickness in AI group was statistically significant (p = 0.000). When compared the values before AI, the number of patients who had osteoporosis was gradually increasing. The decrease was seen in the number of patients with osteopenia. The number of patients with normal lipid profile was gradually increasing up to the second evaluation for tamoxifen group (p = 0.000). On the other hand, the number of patients with hyperlipidemia was increasing for AIs group in follow-up period statistically (p = 0.006). Conclusions : With the aid of careful patient follow and effective disease management strategies, the negative effect over the QoL can be minimized and also the greatest benefit from endocrine therapy can be obtained.